Direct measurements of structural forces and twist transitions in cholesteric liquid crystal films with a surface force apparatus - Zheng, W; Perez-Martinez, C; Petriashvili, G; Perkin, S; Zappone, B (Royal Society of Chemistry, 2019)
Using a surface force apparatus, a cholesteric liquid crystal was confined between two crossed cylindrical surfaces that induced strong planar anchoring and normal alignment of the chiral helix. The film thickness and total twist angle of the chiral molecular structure were simultaneously measured using multiple-beam optical interference. As the film thickness was increased and the chiral structure deformed, the twist angle remained almost unchanged until discontinuous changes occurred at critical distances that were equally spaced by one cholesteric half-pitch length. Structural deformations generated oscillatory elastic forces with periodically spaced maxima corresponding to twist transitions. These findings were reproduced using an equilibrium model of cholesteric confinement and force generation. The analysis indicates that the strength of the azimuthal surface anchoring on mica is high, exceeding 0.2 mJ m-2.